Olive oils qualitative evaluation using a potentiometric electronic tongue: a review of practical applications - Dias, L.G. (2018)
Olive oil is a food product highly prone to fraud, including mislabeling of olive oil commercial category, geographical or olive cultivar origin. Several analytical techniques have been reported to assess olive oil quality, authenticity as well as to detect possible adulterations, namely gas-, liquid- and mass-spectrometry chromatography, DNA and spectroscopy based methods. However, in general, these techniques require expensive pre-sample treatments, are time-consuming and need cost equipments and high skilled technicians. So, fast and more cost-effective methods are still needed and their development a challenge. Among these, electrochemical sensors have been proposed within this field of research, including both voltammetric and potentiometric electronic noses and electronic tongues, individually or as a fused methodology. In this study it is intended to review some of the most recent applications described in the literature including those of the research team regarding the application of a potentiometric electronic tongue, containing cross-sensitive lipidic membranes, to discriminate single-cultivar extra-virgin olive oils by cultivar or sensory intensity, showing its range of applicability and the possibility of using this artificial taste sensor as a complementary/alternative methodology for olive oil sensory analysis.